2022
DOI: 10.15386/mpr-2259
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitors use and risk of inflammatory bowel diseases: a meta-analysis of observational studies

Abstract: Background and objective. Proton Pump Inhibitors (PPIs) reduce gastric acid production and they are indicated for myriad gastrointestinal conditions. Prolonged use of PPI has been linked to the risk of inflammatory bowel disease (IBD) though this fact is not well established. We aimed to conduct a systematic review and meta-analysis to estimate the risk of IBD occurrence with PPI use. Methodology. The databases such as PubMed, Scopus, and Cochrane Library were accessed from inception to December 2020. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…However, the use of PPIs may cause dysbiosis of the microbiota. Several studies have indicated a link between the use of PPIs and the development of IBD[ 30 - 32 ]. An extensive analysis of the microbiota has revealed significant similarities in the changes observed in the intestinal microbiota of both IBD patients and PPI users, suggesting that the intestinal microbiota may play a major role in PPI-induced IBD[ 33 ].…”
Section: Mechanisms For Potential Effects Of Ppis On Ibdmentioning
confidence: 99%
“…However, the use of PPIs may cause dysbiosis of the microbiota. Several studies have indicated a link between the use of PPIs and the development of IBD[ 30 - 32 ]. An extensive analysis of the microbiota has revealed significant similarities in the changes observed in the intestinal microbiota of both IBD patients and PPI users, suggesting that the intestinal microbiota may play a major role in PPI-induced IBD[ 33 ].…”
Section: Mechanisms For Potential Effects Of Ppis On Ibdmentioning
confidence: 99%
“…Reducing gastric acid production with PPIs can affect the resistance of the gut microbiota to intestinal infections and even promote intestinal inflammation [25,26]. Indeed, the question arises whether the increased use of PPIs may contribute to the increasing incidence of IBD worldwide [27]. Several observational studies and meta-analyses have confirmed that there may be a possible relationship between IBD and PPI intake, so patients exposed to PPI are at significantly increased risk of IBD [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Proton pump inhibitors (PPIs) are commonly prescribed medications widely used for acid suppression in different gastrointestinal diseases [1][2][3][4][5]. In fact, PPIs constitute the first-line therapy for gastroesophageal reflux disease (GERD), esophagitis, Helicobacter pylori infection, Zollinger-Ellison Disease, and peptic ulcer disease (PUD) [1][2][3][4][5][6][7]. Ever since its introduction to the United States (US) market, the number of PPI users has been increasing annually [3,5,6,8].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, PPIs constitute the first-line therapy for gastroesophageal reflux disease (GERD), esophagitis, Helicobacter pylori infection, Zollinger-Ellison Disease, and peptic ulcer disease (PUD) [1][2][3][4][5][6][7]. Ever since its introduction to the United States (US) market, the number of PPI users has been increasing annually [3,5,6,8]. In 2016 alone, more than 150 million PPIs were prescribed in the US, not counting over-the-counter (OTC) medications [9].…”
Section: Introductionmentioning
confidence: 99%